Learners’ Perception of the Transition to Instructor-Led Online Learning Environments: Facilitators and Barriers During the COVID-19 Pandemic - Kamble, Aakash; Gauba, Ritika; Desai, Supriya; Golhar, Devidas (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2021)
Online learning environments (OLE) continue to expand due to the COVID-19 pandemic and the transition of a majority of educational institutions and universities worldwide from traditional classroom settings to online learning methods. The purpose of this study was to understand the perceptions of learners at a university in India toward the sudden transition from traditional face-to-face learning to an instructor-led OLE due to the pandemic-induced lockdown enforced across India in March 2020. Using a qualitative case study approach, structured interviews were conducted via Microsoft Teams with 35 learners from Savitribai Phule Pune University, a large public university in India. Interviews comprised eight open-ended questions, which were validated by experts. Results indicate that learners accepted the transition toward the OLE. Five key themes arose from the interview data: accessibility and comfort, Internet connectivity, OLE effectiveness, course content, and interactions between students and instructors.  The study provides insights to the researchers with the emergent themes from the research. Also, it carries practical implications concerning implications regarding infrastructure readiness for remote learners, acceptance, and adoption of OLEs by faculty instructors, organizational support, and facilitating conditions.